Mental Health Factors That Guide Individuals to Engage in Overconsumption Behavior During the COVID-19 Pandemic: A Cross-Cultural Study Between USA and Ecuador - Franklin, Velasco; Cintya, Lanchimba; Mariel, Paz y Miño; Pablo, Díaz-Sanchez Juan (Frontiers in Public Health, 2022)
Background: This study tests a framework that examines the role of several mental health factors (mood, well-being, health consciousness, and hoarding) on individuals’ overconsumption behavior under the novel coronavirus context. This examination is relevant to public health literature because it increases our knowledge on how the context of COVID-19 pandemic affects people’s mental health and provides answers to why individuals engage in overconsumption behavior. Additionally, this research also follows a cross-cultural perspective aiming to understand how individuals from different cultural orientations cope with the psychological effects of the COVID-19 pandemic. Methods: This is a cross-sectional study that compares samples from two countries: Ecuador (n = 334) and USA (n = 321). Data was collected via an online survey. The timing of data collection was set during the mandatory lockdowns and social distance measures taken by both countries to fight against the COVID-19 virus breakout. Partial least squares structural equation modelling was used to test the theorized framework. Multi-group analysis was used to explore cultural orientation differences among the relationships included in the model. Results: The results indicate that individuals’ mood state has a positive relationship with health consciousness, as people try to regulate their health concerns by maintaining positive perceptions of their subjective well-being. Further, the increased concern individuals express in their health is responsible for them to engage in overconsumption behavior. Cultural orientation (individualism vs. collectivism) moderates the relationship between mood and health consciousness. No moderation effect was found for the relationship between health consciousness and overconsumption. Conclusions: The COVID-19 pandemic has generated negative effects in individuals’ mental health. Findings from this study suggest that maintaining a positive mood is important for individuals at the time of mandatory lockdowns, and this effort is related to a greater concern and awareness of their health. Further, health consciousness is responsible to stimulate overconsumption behavior. This chain of effects can be explained by individuals’ interest in their well-being. Culture plays a role in these effects. People from individualistic countries (USA) compared to people from collectivistic countries (Ecuador) demonstrate greater motivation in maintaining their positive mood by showing greater health consciousness.